EVALUACIÓN DE LA ASOCIACIÓN DE UNA BUENA HIGIENE ORAL CON HÁBITOS DE AUTOCUIDADO ADECUADOS EN ESCOLARES VINCULADOS A DOS CONCENTRACIONES ESCOLARES DE BUCARAMANGA Y SU ÁREA METROPOLITANA (2018)
Objective: To identify the associations of a good oral hygiene with adequate self-care habits in school children of two Bucaramanga scholar institutions.Material and methods: An observational analytical cross-sectional study was done, in two-hundred-ninety-one school children. The socio demographic variables and self-care habits were evaluated. Chi square and t students test were run. A binomial regression was done for the multivariate analysis.Result: A relationship fourteen times higher was established in school children with at least four self-care habits compared to those children that have three or less habits.Conclusion: Health promotion programs that considered the association between the number of self-care habits can be used as a strategy that will allow to build a complete picture that will include people, health culture and adequate oral health promotion.